"Humanitarian crisis": The Role of Social Networks in the Migratory Process of Adolescent Migrants - Rivera García, Óscar Bernardo (2016)
This article offers a theoretical and methodological alternative to gauge the extent of social networks to determine the influence, investment and distance that makes a child or teenager in the town of Acambay, State of Mexico for help on a migratory journey to the northern border of Mexico. Sizing the potential of networks would notice a negative result when playing unreliable information. Such is the case of the "humanitarian crisis" of migrant children who perform the migration journey with the false hope of receiving political asylum in the United States. To analyze information from a network specialist Software UCINET6 used.